Experimental Implementation of the content in the subject of Design of Experiments for the training of the Industrial Engineer (LACCEI, 2024)
In this article, we worked with the students who took the Design of Experiments (DoE) subject in the academic semesters 2019-1 to 2021-2, both in the face-to-face and non-face-to-face modalities for the training of the Industrial Engineer, in the Faculty of Engineering of the Ricardo Palma University (URP), in Lima, Peru. Likewise, the analysis of the ranking of Peruvian universities that make use of the DoE in their curricular structure was used in order to gain knowledge of the application of the DoE in the university environment. This article describes the experimental implementation of the DoE course as a viable motivational alternative, which included the identification of the problem and the model variables, the formulation of the hypotheses, the materials, the randomization process and repetitions, carrying out the experiment. The results in the ANOVA (analysis of variance) indicate the significant differences between the form of formative evaluation in theory-problems and the evaluation in the resolution of problems supported by the experimental field, constituting the latter as a field capable of generating greater motivation. for students, allowing them to progress in their abilities and skills, as well as overcome their limitations and obtain a greater operational understanding by applying the DoE statistical tool to obtain success in the industry within the professional field. Therefore, this article shows the didactic importance of the DoE subject at the undergraduate level, for the Industrial Engineering program at the URP, intending to encourage other universities so that they can incorporate this subject at the undergraduate level and thus way to take it to the experimental training field, as a great contribution to strengthening the integral of Industrial Engineering students and related programs, contributing to improving the quality of teaching. Finally, it should be noted that the importance of didactics in the teaching and learning processes is fundamental, because it allows educational innovation, so that teaching can achieve a substantial improvement in student learning.